High-energy, stable and recycled molecular solar thermal storage materials using AZO/graphene hybrids by optimizing hydrogen bonds. Issue 39 (20th August 2015) - Luo, Wen; Feng, Yiyu; Qin, Chengqun; Li, Man; Li, Shipei; Cao, Chen; Long, Peng; Liu, Enzuo; Hu, Wenping; Yoshino, Katsumi; Feng, Wei
Abstract : High grafting degree and close-packed interactions enable intermolecular hydrogen bonds for AZO on the surface of graphene nanosheets, resulting in a remarkable increase in storage energy density and stability for solar energy storage. Abstract : An important method for establishing a high-energy, stable and recycled molecular solar heat system is by designing and preparing novel photo-isomerizable molecules with a high enthalpy and a long thermal life by controlling molecular interactions. A meta - and ortho -bis-substituted azobenzene chromophore (AZO) is covalently grafted onto reduced graphene oxide (RGO) for solar thermal storage materials. High grafting degree and close-packed molecules enable intermolecular hydrogen bonds (H-bonds) for both trans -( E ) and cis -( Z ) isomers of AZO on the surface of nanosheets, resulting in a dramatic increase in enthalpy and lifetime. The metastable Z -form of AZO on RGO is thermally stabilized with a half-life of 52 days by steric hindrance and intermolecular H-bonds calculated using density functional theory (DFT). The AZO–RGO fuel shows a high storage capacity of 138 Wh kg −1 by optimizing intermolecular H-bonds with a good cycling stability for 50 cycles induced by visible light at 520 nm. Our work opens up a new method for making advanced molecular solar thermal storage materials by tuning molecular interactions on a nano-template.